Grain Mineral Accumulation Changes in Chinese Maize Cultivars Released in Different Decades and the Responses to Nitrogen Fertilizer - Guo, Song; Chen, Yanhua; Chen, Xiaochao; Chen, Yanling; Yang, Lan; Wang, Lifeng; Qin, Yusheng; Li, Mingshun; Chen, Fanjun; Mi, Guohua; Gu, Riliang; Yuan, Lixing (Frontiers in Plant Science, 2020)
Evaluating changes in the accumulation of grain minerals, including nitrogen (N), copper (Cu), iron (Fe), potassium (K), magnesium (Mg), manganese (Mn), phosphorus (P), and zinc (Zn), across different genotypes can provide valuable information for the development of nutrient-enriched maize varieties. Meanwhile, N rates can affect maize yield and quality, but their effects on element accumulation remain to be elucidated. Here, field experiments were conducted at three locations in China over two years (2010 and 2011). Under a normal N application rate (240 kg N ha-1), 24 maize hybrids that had been bred and released between 1930 and 2010 were evaluated for the elemental concentrations in their grains. Old (1930-1990) and new (1991-2010) era maize hybrids were selected to investigate grain element accumulation in response to different levels of N (0, 60, 120, 180, and 240 kg N ha-1). The results showed that element concentrations were significantly affected by genotype, year, N rates and their interactions. Grain yield tended to increase with the year of hybrid release, while the concentrations of N, Cu, Mn, and Zn in the grain significantly declined in the more modern varieties. The element concentrations of grains were mainly influenced by N rate or N × year interactions. As N levels increased, N, Cu, Fe, and Mn concentrations rose, while K, P, Zn and Mg concentrations decreased. Compared with old-era hybrids, new-era hybrids showed an increase in grain yield of 26.08%; however, they demonstrated decreases in Fe, Zn, Cu, and N concentrations of 10.01%, 11.93%, 21.09%, and 8.25%, respectively. In the modern varieties the reduction in Cu, P, K, and Zn concentrations were significantly exacerbated by high N rates, but this was not the case in the old varieties, except for Zn. However, the optimal N rate (120 kg N ha-1) could increase N, Fe, Mg, and Mn concentrations without affecting grain yield in the modern varieties. It is concluded that maize breeding processes have improved grain yield, but reduced grain nutrient element concentrations. Enhanced concentrations of certain elements in maize grain could be achieved with optimal rates of N fertilizer being applied.